Konstruksi Pick Me Girl Dalam Video Klip “Dear Future Husband” Meghan Trainor - Wijaya, Edi; Sejati, Taqwa (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The video clip becomes a creative outlet for conveying the singer's message, which is done together with the director he chooses. It is not uncommon for video clips to be realized as jokes, short films, criticism and even social lessons contained in the story. The video clip is also a realization of the lyrics sung and is part of its construction. This research is a type of qualitative descriptive research which uses a communication science approach, specifically focusing on mass communication, one of the research objects is a video clip of Dear Futur Husband belonging to the American singer, Meghan Trainor. Researchers use the theory of social reality construction in mass media as the theory underlying this research. Meanwhile, the paradigm used is the Constructivism paradigm with a qualitative approach. The method used is the content analysis method with Charles Sanders Peirce's semiotics as the analysis technique and observation is also of course documentation to strengthen and serve as authentic evidence. Meanwhile, the sources for this research also come from the video clip in question, the researcher's book, as well as several search results for research supporting articles on confirmed website pages as well as supporting documents both outside the network and in other networks. The next step taken by researchers was to immediately analyze the collected data. The results of the analysis are data education regarding the theory used, explanations and conclusions from the researcher.